Slavery, Fatherhood, and Paternal Duty in African American Communities over the Long Nineteenth Century - Hilde, Libra Rose (John Hope Franklin series in African American history and culture., 2020)
"Analyzing published and archival oral histories of formerly enslaved African Americans, Libra R. Hilde explores the meanings of manhood and fatherhood during and after the era of slavery, demonstrating that black men and women articulated a surprisingly broad and consistent vision of paternal duty across more than a century. Complicating the tendency among historians to conflate masculinity within slavery with heroic resistance, Hilde emphasizes that, while some enslaved men openly rebelled, many chose subtle forms of resistance in the context of family and local community. She explains how a significant number of enslaved men served as caretakers to their children and shaped their lives and identities. From the standpoint of enslavers, this was particularly threatening--a man who fed his children built up the master's property, but a man who fed them notions of autonomy put cracks in the edifice of slavery"--